2011
DOI: 10.1097/iae.0b013e31820f4b39
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Fellow Eyes of Patients With Central Serous Chorioretinopathy

Abstract: The subfoveal choroid in the fellow eyes of patients with CSC was thicker in the eyes with choroidal vascular hyperpermeability. Enhanced depth imaging spectral-domain optical coherence tomography can assess the effects of choroidal vascular hyperpermeability by measuring the choroidal thickness noninvasively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(204 citation statements)
references
References 24 publications
12
186
1
5
Order By: Relevance
“…11 EDI-OCT, which enabled apparent visualization of choroidal vasculature, showed increased subfoveal thickness in eyes with CSC. [11][12][13][14][15][16] This study showed that the thickness of choroid in the eyes with CSC decreased after spontaneous disappearance of SRF; however, not to those of the normal level. This result corresponds to the previous study, which demonstrated the persistent choroidal vascular abnormalities on ICGA, even after the resolution of active leakage from the level of RPE.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…11 EDI-OCT, which enabled apparent visualization of choroidal vasculature, showed increased subfoveal thickness in eyes with CSC. [11][12][13][14][15][16] This study showed that the thickness of choroid in the eyes with CSC decreased after spontaneous disappearance of SRF; however, not to those of the normal level. This result corresponds to the previous study, which demonstrated the persistent choroidal vascular abnormalities on ICGA, even after the resolution of active leakage from the level of RPE.…”
Section: Discussionmentioning
confidence: 59%
“…[4][5][6][7][8][9] Furthermore, recent studies evaluated the choroidal thickness in CSC using enhanced depth imaging optical coherence tomography (EDI-OCT), which can provide crosssectional images of choroid non-invasively and assess the effects of choroidal vascular hyperpermeability. [10][11][12][13][14][15][16] Imamura et al 11 reported that subfoveal choroidal thickness (SFCT), in eyes with CSC, was significantly larger than that of the normal eyes, as shown on EDI-OCT. Previous studies showed that the two treatment modalities, PDT and focal laser photocoagulation, resulted in different changes on the choroidal thickness; EDI-OCT showed decrement of choroidal thickness after PDT, whereas it did not after laser photocoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 and 222.6 μm, respectively) in our study was less than that in the previous study, 20 this difference between the studies may have been caused by differences in the measurement software, the OCT light source, the patient profile (e.g., age). Maruko et al 3,4 performed ICGA and found that subfoveal choroidal thickness in the fellow eyes of patients with central serous chorioretinopathy was increased in the eyes with choroidal vascular hyperpermeability. They suggested that hyperpermeability causes choroidal thickening through accumulation of fluid and that dilation of choroidal vessels plays a partial role in the choroidal thickening.…”
Section: Resultsmentioning
confidence: 99%
“…7 It has been demonstrated that enhanced depth imaging (EDI) SD-OCT, which produces an inverted image from 100 scans to improve signal-to-noise ratio, can be used to visualize the choroid even better. [8][9][10][11] The new technology has lead to better understanding of the role of choroid in various macular diseases, including central serious chorioretinopathy, 9-11 high myopia, 12,13 Vogt-Koyanagi-Harada disease, 14 and a variety of retinal dystrophies. 15 However, although SD-OCT has been used to assess choroidal thickness in various diseases, including AMD, it has not yet been used to correlate choroidal thickness with drusen load in dry AMD.…”
Section: Introductionmentioning
confidence: 99%